Organisational Belonging and Identity of Remote Workers - Bedoshvili, Mariam; Schmitt, Judith; Kania, Karolina Anna; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores how remote workers experience organizational belonging and identity in the absence of traditional office environments. As remote work becomes a normalized structure rather than a temporary response, questions arise about how connection, visibility, and inclusion are sustained when physical presence is no longer part of daily work. Using a qualitative approach based on semi-structured interviews with five remote workers in various roles and industries, this study applies thematic analysis to uncover how individuals navigate emotional connection, recognition, and self-discipline in remote contexts. The findings suggest that belonging in remote work is not built by replicating traditional office culture through digital means but by rethinking what organizational life looks like altogether. Participants emphasized that authentic connection in remote settings depends less on mimicking in-person rituals and more on purposeful, human-centered structures that recognize individuality, foster emotional safety, and build shared meaning across distance. Ultimately, the research shows that belonging in remote work does not emerge automatically — it has to be deliberately built through thoughtful communication, intentional leadership, and workplace cultures that are designed with distance in mind.
Vedoucí práce: Judith Schmitt
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses